Emission and Absorption Tuning in TADF B, N‐Doped Heptacenes: Toward Ideal‐Blue Hyperfluorescent OLEDs. Issue 17 (14th June 2022) - Stavrou, Kleitos; Madayanad Suresh, Subeesh; Hall, David; Danos, Andrew; Kukhta, Nadzeya A.; Slawin, Alexandra M. Z.; Warriner, Stuart; Beljonne, David; Olivier, Yoann; Monkman, Andrew; Zysman‐Colman, Eli
Abstract: Developing high‐efficiency purely organic blue organic light‐emitting diodes (OLEDs) that meet the stringent industry standards is a major current research challenge. Hyperfluorescent device approaches achieve in large measure the desired high performance by combining the advantages of a high‐efficiency thermally activated delayed fluorescence (TADF) assistant dopant with a narrowband deep‐blue multi‐resonant TADF (MR‐TADF) terminal emitter. However, this approach requires suitable spectral overlap to support Förster resonance energy transfer (FRET) between the two. Here, a color tuning of a recently reported MR‐TADF B, N‐heptacene core through control of the boron substituents is demonstrated. While there is little impact on the intrinsic TADF properties—as both singlet and triplet energies decrease in tandem—this approach improves the emission color coordinate as well as the spectral overlap for blue hyperfluorescence OLEDs (HF OLEDs). Crucially, the red‐shifted and more intense absorption allows the new MR‐TADF emitter to pair with a high‐performance TADF assistant dopant and achieve maximum external quantum efficiency (EQEmax ) of 15% at color coordinates of (0.15 and 0.10). The efficiency values recorded for the device at a practical luminance of 100 cd m –2 are among the highest reported for HF TADF OLEDs with CIEy  ≤ 0.1. Abstract : Pairing terminal emitters with suitable assistant dopants in hyperfluorescence organic light‐emitting diodes can be restrictive. Here, exchanging boron substituents simultaneously tunes both the emission and absorption spectra of a multi‐resonant TADF B, N‐heptacene, allowing use with available blue TADF cohosts. This approach may circumvent the need for deeper‐blue TADF cohosts by instead expanding hyperfluorescence compatibility to more stable cyan or green materials.